2015
DOI: 10.1016/j.jssc.2014.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Atomic charges for modeling metal–organic frameworks: Why and how

Abstract: Atomic partial charges are parameters of key importance in the simulation of Metal-Organic Frameworks (MOFs), since Coulombic interactions decrease with the distance more slowly than van der Waals interactions. But despite its relevance, there is no method to unambiguously assign charges to each atom, since atomic charges are not quantum observables. There are several methods that allow the calculation of atomic charges, most of them starting from the wavefunction or the electronic density or the system, as ob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 122 publications
0
63
0
Order By: Relevance
“…Comparison to the semi-empirical EQeq method showed large differences to the charges calculated by the DDEC method, leading to possible inaccuracies in adsorption modelling. Hamad et al found that simulations with different charges led to difference in thermal expansion results, thus showing that the choice of framework point charges can also affect modelling of structural properties of MOFs (Hamad et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Comparison to the semi-empirical EQeq method showed large differences to the charges calculated by the DDEC method, leading to possible inaccuracies in adsorption modelling. Hamad et al found that simulations with different charges led to difference in thermal expansion results, thus showing that the choice of framework point charges can also affect modelling of structural properties of MOFs (Hamad et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Ionescu and coworkers [190] argued that partial atomic charges are a well-established concept and are very useful in understanding and modeling the chemical reactivity behavior of molecules, ranging from simple compounds, to crystals, to large drug-like molecules, to biomacromolecular complexes with hundreds of thousands of atoms. Hamad et al [191] found that knowledge of atomic charges on specific systems is important, and that they are useful in gaining insight into metal-organic frameworks (MOFs). The strategy, which is applicable to other porous materials, paves the way for large-scale computational screening of MOFs for specific applications as well as contributing to a better understanding of the structure-property relationships for MOFs, eventually assisting in their development and application [192].…”
Section: Is the Concept Of Atomic Charge Meaningful?mentioning
confidence: 99%
“…Since the definition of partial atomic charges is not strict, various models of partial atomic charges can, however, differ significantly in the reliability of their predictions. Therefore, an evaluation of the performance of a partial atomic charge model for a given problem is necessary before using it for making reliable predictions [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%